2014
DOI: 10.1002/isaf.1355
|View full text |Cite
|
Sign up to set email alerts
|

A Psychological Approach to Microfinance Credit Scoring via a Classification and Regression Tree

Abstract: Microfinance institutions' (MFIs') peculiar lending methodology is characterized by an unchallenged decisionmaking predominance from the part of loan officers. Indeed, the latter are in charge of providing a great deal of diagnostic information regarding the entrepreneur's psychological traits likely to help them run a business. This paper constitutes an initial attempt towards exploring the role of borrowers' psychological traits in predicting future default occurrences. It builds on a nonparametric credit sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 43 publications
2
13
0
1
Order By: Relevance
“…Olawande (2011, p. 4) It is unsurprising, then, that this topic has attracted researchers' attention. Indeed, there have been several contributions on this topic in the literature, from areas ranging from marketing, consumer behavior and psychology to finance (Anikeeff, 1996;Chye, Chin, & Peng, 2004;Burnaz & Topcu, 2011;Ju, Wenbin, & Bei, 2011;Baklouti, 2014), and using different methodologies. These studies have allowed several determinants able to predict a "good" tenant to be identified, namely: the tenant's annual income, credit access and psychological profile (cf.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Olawande (2011, p. 4) It is unsurprising, then, that this topic has attracted researchers' attention. Indeed, there have been several contributions on this topic in the literature, from areas ranging from marketing, consumer behavior and psychology to finance (Anikeeff, 1996;Chye, Chin, & Peng, 2004;Burnaz & Topcu, 2011;Ju, Wenbin, & Bei, 2011;Baklouti, 2014), and using different methodologies. These studies have allowed several determinants able to predict a "good" tenant to be identified, namely: the tenant's annual income, credit access and psychological profile (cf.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, reported AUC values vary largely across different studies; therefore, reference values are to be considered with caution (e.g. Baklouti, 2014;Blanco et al, 2013;van Gool et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Madhavi and Radhamani (2014) report that support vector machines had the highest accuracy in their study, while Baklouti (2014) advocates a classification and regression tree, which outperforms discriminant analysis and logistic regression. In contrast, Cubiles de la Vega et al (2013) compared classification trees, ensemble methods, linear and quadratic discriminant analysis, logistic regression, multilayer perceptron, and support vector machines, and found that multilayer perceptron performs the best.…”
Section: Empirical Model Buildingmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers found that the model helped reduce the proportion of bad loans classified as good loans by 3.125%, which leads to a decrease in MFIs' losses by 4.8%. The model outperforms the classic techniques by 6.8 and 13.5% compared to the discriminant analysis and logistic regression models, respectively (Baklouti, 2014).…”
Section: The Tasks Of Ai In Finance and Financial Marketsmentioning
confidence: 99%